Epilogue: ten thousand : satirical themes and variations seen transculturally - Mittler, Barbara (Asian Punches, 2013)
China’s illustrated magazines, which came into being in the mid-1880s, quickly became part of a community of illustrated papers from all over the world. These publications knew of each other, they would reprint each other’s illustrations and they would quote each other’s articles as a way to improve and authenticate their global coverage.
First Online: 25 July 2012
Gesehen am 17.11.2020